Empowerment of Village Cooperative Enterprises For Economic Resilience During The Covid 19 - Zakiy, Muhammad; Khasanah, Miftakhul (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
The Covid 19 has changed the routine of the global community, including in Indonesia. This service program aimed to empower and develop the potential of village cooperative members, especially during the Covid 19 pandemic, especially in Kasihan village. This program was carried out in 3 stages, handwashing soap manufacture training, production of products to be marketed, and organizational training. The output of this program is the creation of ready-to-sell products, business and marketing strategies, packaging that meets health standards. The development of village cooperatives for the welfare of cooperative members is also the output of this empowerment program. Partners in this service program are the Kasihan hamlet community who are members of the Harum Manis Cooperative. The choice of this partner was chosen because the problems that the community has in the midst of the Covid 19 pandemic are very urgent to find a solution, and the Harum Manis has just started a business so that business programs are needed to develop. In order to achieve the success of this activity, material delivery, discussion and practical training, business and marketing training had been carried out. The steps were through observation of the service team to partner villages, delivery of organizational materials, workshops and mentoring, and post-program monitoring.